Global Economic Transformation During COVID-19: A Systematic Literature Review - Kharisma Hijriyatul Amelia; Salahudin Salahudin; Syamsul Rizal; Devita Prinanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This study aims to analyze the impact caused by the global economic crisis, precisely the effect caused by the Covid-19 pandemic. The research method uses a systematic literature review, using 70 scientific articles sourced from Scopus data using the Vosviewer application. The study results reveal that the transformation of the world economy after the spread of the Covid-19 virus has experienced a very significant decline, such as the Economic Growth Index in 2019. The main focus for economic actors is to stabilize the world economy. The results of this study contribute to the development of policy analysis to address the threat of a world economic recession. There are limitations in this research in the use of sources that only use the Scopus database, which is undoubtedly less diverse and non-specific. So this study cannot describe the overall economic transformation that has occurred worldwide using VOS viewer and Mendeley applications to process data. As well as in subsequent research, it is necessary to use scientific articles sourced from other reputable international databases such as the Web of Science and Dimensioned Scholars.